Interaction of photons with molecules of glucose and fructose - Bandurin, Yu.A.; Popik, T.Yu.; Zavilopulo, A.N. (Reports of the National Academy of Sciences of Ukraine, 2022)
The luminescence spectra of glucose and fructose molecules in the spectral region λ = 400÷700 nm at different excitation energies are studied using a Shimadzu RF-6000 spectrofluorophotometer. The source of photons that excite the luminescence of the studied molecules in the spectral interval 250 ÷ 400 nm was a xenon lamp. The samples were irradiated by photons with the following wavelengths: λext = 275, 323, 354, and 380 nm. The energies of photons with these wavelengths are close to the binding energies of the corresponding diatomic fragments of glucose and fructose molecules. For the first time, differences were found both in the quantum yield of luminescence of these molecules and in the positions of the radiation maxima. The analysis of these differences is carried out, and it is shown that the difference in the structures of glucose and fructose molecules significantly affects their luminescent properties.